Dead ringer : a novel - Hauty, Chris (Emily Bestler/Atria Books, 2025)
A conspiracy - whose roots lead back to the fateful events of November 22, 1963 - could change the course of the nation... and the world. Almost five decades later, a disgraced former Secret Service officer and a Jesuit professor join forces to delve into the mysteries surrounding the events of November 22, 1963. Fixated on deciphering the conspiracies behind the history-changing assassination, they are oblivious to the fact that the cabal is still active - and may face an end as bloody as the carnage in Dealey Plaza. Will Mingus and Verdugo be able to uncover the truth in time? Or will they become two more footnotes in history?